Mixed‐Linkage Glucan Oligosaccharides Produced by Automated Glycan Assembly Serve as Tools To Determine the Substrate Specificity of Lichenase. Issue 13 (3rd February 2017) - Dallabernardina, Pietro; Schuhmacher, Frank; Seeberger, Peter H.; Pfrengle, Fabian
Abstract: The mixed‐linkage (1→3), (1→4)‐d ‐glucan (MLG) specific glycosyl hydrolase lichenase is an important biochemical tool for the structural characterization of MLGs. It holds potential for application in the brewery, animal feed, and biofuel industries. Several defined MLG oligosaccharides obtained by automated glycan assembly are used to analyze the substrate specificities of Bacillus subtilis lichenase. Two glucose building blocks (BBs), equipped with a temporary fluorenylmethyloxycarbonyl chloride (Fmoc) protecting group in the C‐3 or C‐4 position, served to assemble different oligosaccharides by using an automated oligosaccharide synthesizer. Light‐induced cleavage of the glycan products from the solid support followed by global deprotection provided seven MLG oligosaccharides of different length and connectivity. After incubation of the MLG oligosaccharides with lichenase, the digestion products were analyzed by HPLC‐MS. These digestion experiments provided insights into the enzyme's active site that is in line with other recent evidence suggesting that the substrate specificity of lichenases has to be reconsidered. These results demonstrate that synthetic MLG oligosaccharides are useful tools to analyze mixed‐linkage β‐glucanases. Abstract : Assembly and deconstruction : The automated glycan assembly of mixed‐linkage glucan oligosaccharides as biochemical tools for analyzing the substrate specificities of lichenase and other mixed‐linkage β‐glucanases is reported (see scheme).